On Meromorphic Solutions of Nonlinear Complex Differential Equations (Communications in Mathematical Research, 2019)
Applying the Nevanlinna theory of meromorphic function, we investigatethe non-admissible meromorphic solutions of nonlinear complex algebraic differentialequation and gain a general result. Meanwhile, we prove that the meromorphic solutions of some types of the systems of nonlinear complex differential equations arenon-admissible. Moreover, the form of the systems of equations with admissible solutions is discussed.